Proces wyboru strategicznego - kluczowy etap zarządzania strategicznego - Kaleta, Andrzej (The strategic choice process as the a key element in strategic management, 2006)
Strategy formulation means choosing the optimal strategic option and is always the key point in the strategic management process. The strategic choice process consists of creation of development ideas which then get transformed into strategic options out of which one is chosen for implementation. This choice will never be final and should be continuously verified. In business practice the choice of the attractive development concept can be difficult and this is why it is worthwhile to improve the strategic choice process even if there is no chance for creating a universal procedure.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 72-84